Evaluating the interrelations between the autism polygenic score and psychiatric family history in risk for autism. Issue 1 (19th October 2021) - Schendel, Diana; Munk Laursen, Thomas; Albiñana, Clara; Vilhjalmsson, Bjarni; Ladd‐Acosta, Christine; Fallin, Margaret Danielle; Benke, Kelly; Lee, Brian; Grove, Jakob; Kalkbrenner, Amy; Ejlskov, Linda; Hougaard, David; et al.
Abstract: Psychiatric family history or a high autism polygenic risk score (PRS) have been separately linked to autism spectrum disorder (ASD) risk. The study aimed to simultaneously consider psychiatric family history and individual autism genetic liability (PRS) in autism risk. We performed a case–control study of all Denmark singleton births, May 1981–December 2005, in Denmark at their first birthday and a known mother. Cases were diagnosed with ASD before 2013 and controls comprised a random sample of 30, 000 births without ASD, excluding persons with non‐Denmark‐born parents, missing ASD PRS, non‐European ancestry. Adjusted odds ratios (aOR) were estimated for ASD by PRS decile and by psychiatric history in parents or full siblings (8 mutually‐exclusive categories) using logistic regression. Adjusted ASD PRS z ‐score least‐squares means were estimated by psychiatric family history category. ASD risk (11, 339 ASD cases; 20, 175 controls) from ASD PRS was not substantially altered after accounting for psychiatric family history (e.g., ASD PRS 10th decile aOR: 2.35 (95% CI 2.11–2.63) before vs 2.11 (95% CI 1.91–2.40) after adjustment) nor from psychiatric family history after accounting for ASD PRS (e.g., ASD family history aOR: 6.73 (95% CI 5.89–7.68) before vs 6.32 (95% CI 5.53–7.22) after adjustment). ASD risk from ASD PRS varied slightly by psychiatric family history. While ASD risk from psychiatric family history was not accounted for by ASD PRS and vice versa, risk overlap between the two factors will likely increase as measures of genetic risk improve. The two factors are best viewed as complementary measures of family‐based autism risk. Lay Summary: Autism risk from a history of mental disorders in the immediate family was not explained by a measure of individual genetic risk (autism polygenic risk score) and vice versa. That is, genetic risk did not appear to overlap family history risk. As genetic measures for autism improve then the overlap in autism risk from family history versus genetic factors will likely increase, but further study may be needed to fully determine the components of risk and how they are inter‐related between these key family factors. Meanwhile, the two factors may be best viewed as complementary measures of autism family‐based risk.